Desain Inovasi Pendidikan yang Berpihak Pada Peserta Didik dan Memerdekakan Peserta Didik Abad 21 - Mediana, Verga; Agustiani, Iis; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Ki Hadjar Dewantara, an Indonesian educational figure, is renowned for his holistic approach to education through the concept of